Use of Blue-Green Fluorescence and Thermal Imaging in the Early Detection of Sunflower Infection by the Root Parasitic Weed Orobanche cumana Wallr. - Ortiz-Bustos, Carmen M.; Pérez-Bueno, María L.; Barón, Matilde; Molinero-Ruiz, Leire (Frontiers in Plant Science, 2017)
Although the impact of Orobanche cumana on sunflower (Helianthus annuus L.) becomes evident with emergence of broomrape shoots aboveground, infection occurs early after sowing, the host physiology being altered during underground parasite stages. Genetic resistance is the most effective control method and one of the main goals of sunflower breeding programmes. Blue-green fluorescence (BGF) and thermal imaging allow non-destructive monitoring of plant diseases, since they are sensitive to physiological disorders in plants. We analysed the BGF emission by leaves of healthy sunflower plantlets, and we implemented BGF and thermal imaging in the detection of the infection by O. cumana during underground parasite development. Increases in BGF emission were observed in leaf pairs of healthy sunflowers during their development. Lower BGF was consistently detected in parasitised plants throughout leaf expansion and low pigment concentration was detected at final time, supporting the interpretation of a decrease in secondary metabolites upon infection. Parasite-induced stomatal closure and transpiration reduction were suggested by warmer leaves of inoculated sunflowers throughout the experiment. BGF imaging and thermography could be implemented for fast screening of sunflower breeding material. Both techniques are valuable approaches to assess the processes by which O. cumana alters physiology (secondary metabolism and photosynthesis) of sunflower.